Nutraceutical and phytotherapy supplementation in the treatment of fibromyalgia: literature review (Research, Society and Development, 2021)
Fibromyalgia (FB) is a multifactorial disease that affects a large portion of the population and still has its diagnosis as a subject of controversy. It is characterized by chronic pain in multiple points of the body. This article aimed to identify nutraceutical supplements that could contribute to the treatment of FB in its multiple aspects and thus improve the quality of life of the patients. The bibliographic survey was limited to searches for articles in Portuguese and English in the PubMed, SciELO and LILACS databases published between January 2015 and March 2020. The most commonly found active ingredients were coenzyme Q10, 25-hydroxyvitamin D, probiotics (Lactobacillus Rhamnosus, Casei, Acidophilus and Bifidobacterium Bifidus) and phytotherapic medicines such as ginger, acerola cherry, Spiraea Ulmaria, passiflora, Elymus repens in association with other products, Crocus Sativus (saffron) and also Ganoderma lucidum, a kind of mushroom. It is of fundamental importance to understand how supplements can help in the treatment of fibromyalgia, promoting a more natural therapy, less expensive and with less side effects for its patients.